Violation in the axis of the "microbiota of the digestive tract-brain" under conditions of ischemia-reperfusion of the brain (literature review) - Tkachuk, O.; Tkachuk, S.; Povar, M.; Denysenko, O.; Shtefaniuk, V. (Journal of Education, Health and Sport, 2021)
The aim of the study is to analyze current views concerning interrelations between the state of intestinal microbiota and the course of ischemic-reperfusion brain injury. Conclusion. Literary data are indicative of disputable scientific opinions existing nowadays concerning the role of dysbacteriosis (neuroprotective or neurodegenerative) in the course of ischemic brain injuries. Meanwhile, the studies are in common concerning the evidenced role of the intestinal microbiota in disturbances of T-cell homeostasis, ratio changes of their Treg-Th17 subpopulations, and migration of intestinal lymphocytes to the ischemic brain.